Find the remainder when x + 3x² + 3x + 1 is divided by
1
(i) x+1
(ii) x-1\2
(iii) x
Answers
Answer:
Step-by-step explanation:
(3x² + 3x + x + 1 )/ 1
= (3x² + 3x + x + 1 )
= 3x ( x + 1 ) + 1 ( x + 1 )
= ( 3x + 1 ) ( x + 1 )
the factors are ( 3x + 1 ) ( x + 1 )
the answer is (i)
Step-by-step explanation:
Given:
Find the remainder when x³ + 3x² + 3x + 1 is divided by —
(i) x + 1 (ii) x-1/2
1st solution:- The divisor here is x + 1 = x-(-1)
So, by remainder theorem, when p(x) is divided by x+1, the remainder is p(-1)
➠p(x) = x³ + 3x² + 3x + 1
➠ p(-1) = (-1)³ + 3(-1)² + 3(-1) + 1
= -1 + 3 - 3 + 1
= 0
Hence, the required remainder is 0.
2nd Solution:- The divisor here is x-½ [From x - a with a = ½
So, by remainder theorem, when p(x) is divided by x-½, the remainder is p(½).
➠ p(x) = x³ + 3x² + 3x + 1
➠ p(½) = (½)³+ 3(½) + 3(½) + 1
= ⅛ + ¾ + ³/² + 1
= 27/8
Hence, the required remainder is 27/8.